Damping derivative evaluation in pitch for an ogive at high mach numbers - Shabana, Aysha; Monis, Renita Sharon; Crasta, Asha; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In this paper, the formulae for damping derivative for an ogive with the suppositions of a curve on the conical nose. The damping derivative in pitch is assessed for a broad scope of the inertia levels and the flow deflection angle. The outcome indicates that there is a progressive increase in the damping derivative with an increase in the flow deflection angle. When the inertia level is increased from M = 5 to 9, the damping derivative value diminishes, it becomes independent of inertia level, and later any increase in the Mach number does not yield any change in the magnitude of the damping derivatives, and that indicates the attainment of the Mach number independence principle. It is found from the results that when ogive is superimposed, the positive slope is useful, whereas, the negative slope does not yield any useful results, hence must be avoided in the design of the nose part of the aerospace vehicle design. Due to both either positive or negative slope, there is a considerable shift in the Centre of the pressure of the nose, which is right from the dynamic stability point of view. When the slope increased beyond λ > 10, the pressure distribution is such that the magnitude of the damping derivatives attains very peculiar behavior, and this trend is not acceptable. Hence, such a high value of the λ must be avoided.